Changing students' perceptions of people with mental illness - Frailing, Kelly (Applied psychology in criminal justice, 2016)
Research reveals negative attitudes toward people with mental illness among the generalpublic and among people who work with this group. However, there is a dearth of literatureon criminal justice and criminology students' attitudes toward this group. The presentresearch reports on the measurement of criminal justice and criminology students' attitudestoward people with mental illness before and after a class on the criminalization of thisgroup. Results reveal significantly more positive attitudes toward people with mental illnessat the conclusion of the class. These results are encouraging; current criminal justice andcriminology students are likely to encounter people with mental illness in their future fieldor academic work, and more positive attitudes are an important step in stigma reduction.